2004
DOI: 10.1016/j.jsg.2003.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Calcite twin morphology: a low-temperature deformation geothermometer

Abstract: Twinning of the e-plane is the dominant crystal -plastic deformation mechanism in calcite deformed below about 400 8C. Calcite in a twin domain has a different crystallographic orientation from the host calcite grain. So-called thin twins appear as thin black lines when viewed parallel to the twin plane at 200-320 £ magnification under a petrographic microscope. Thick twins viewed in the same way have a microscopically visible width of twinned material between black lines. Calcite e-twin width and morphology h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
268
0
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(296 citation statements)
references
References 27 publications
14
268
0
14
Order By: Relevance
“…We use the fact that twin width and twin type correlate directly with temperatures of deformation (e.g. Ferrill, 19991;Burkhard, 1993;Ferrill et al, 2004). Thin twins (< 1 !m) dominate below 170° C and thick twins dominate above 200° C, whereas above 250° C dynamic recrystallization becomes more important (Ferrill et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…We use the fact that twin width and twin type correlate directly with temperatures of deformation (e.g. Ferrill, 19991;Burkhard, 1993;Ferrill et al, 2004). Thin twins (< 1 !m) dominate below 170° C and thick twins dominate above 200° C, whereas above 250° C dynamic recrystallization becomes more important (Ferrill et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…However, the linear stress gradient models appear to confirm both the lower values of stress from the samples and the most likely burial depths as those giving the most physically realistic stress values. twinning in all samples, including the borehole, is of type 1 or 2 (mostly type 1) (burkhard 1993;Ferrill et al 2004) except for clearly reworked grains from the Helvetic nappes, suggesting low temperature (<150 °c) deformation and hence burial likely < 5 km.…”
Section: Strength Of the Jura-molasse Systemmentioning
confidence: 91%
“…The stripping procedure was used in cases of high proportions of NEVs and a large number of measured grains. An experimental reevaluation of the CSGT has shown that measurements of about 50 grains on one thin section or 25 grains on two mutually perpendicular thin sections yield the best results (Groshong et al 1984;Evans and Groshong 1994;Ferrill et al 2004). The chance to extract the records of more than two deformations from one data set is limited when dealing with natural rocks (Burkhard 1993).…”
Section: Methodsmentioning
confidence: 99%